Problems and Prospects of Improving the Education of the Spiritual Values of Students under the Conditions of Higher Educational Establishment (HEE) of Non-Humanitarian Profile - Violetta Lappo (Pedagogical Discourse, 2015)
The article deals with the problems of teaching spiritual values to students, obtaining the profession of non-humanitarian profile. On the basis of theoretical and structural analysis, the concept «spiritual values education student's personality» has been determined. This concept has fundamental-philosophical foundation, special functional features (regulatory, resultiveness, dynamism, complexity, consistency), and through various forms, methods and means it realizes educational influence on emotions, world outlook, way and quality of life, values, readiness for self-perfection of both, the individual and the society. It is cleared out that the purpose of teaching  spiritual values of students is in the training of specialists capable to think ethically, to exercise moral choice, to make moral decisions, ready for active work on spiritual self-improvement. It is determined that the task of educating the spiritual values of students, regardless of specialty and directions of training involves: improving the culture of ethical thinking, providing positive motivation for self-improvement; inclusion in the process of interaction with the environment for the formation of the ability to display feelings of deep hearty affection, implementation of the moral act.The article explains the thesis about the necessity of creation of special educational programs, aimed at improving the process of formation of spiritually-valuable sphere of the personality of the student.